Analysis Of Customer Satisfaction On The Marketing Mix Of Halo Telkomsel Wonosobo, Central Java - Enny Istanti; Mahjudin Mahjudin; Rina Dewi; Diana Zuhro; Sutini Sutini; Achmad Daengs GS (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
This research aims to examine what factors influence the level of customer loyalty of GeraiHALO Telkomsel Wonosobo, Central Java. The population in this study are customers who have subscribed or are currently subscribing to Telkomsel Kartu HALO, simPATI and AS product services, having subscribed for at least six months. Determining the sample in this research used the probability sampling method. This analysis uses the Importance Performance Analysis (IPA) method which is used to determine the level of importance and perception (expectations) of the Marketing Mix towards customer satisfaction implemented by the company. The results of the IPA analysis show that the dominant factors influencing customer loyalty are product quality, price, distribution variables. and promotion variables in this research are quite good in explaining customer perceptions. The author's advice to companies is that companies create products that are superior in quality, and always maintain product quality, namely by always innovating products that are tailored to customer desires for the product. Apart from that, companies must always pay attention to customer complaints by minimizing customer complaints.